Can Earth's Magnetotail Plasma Sheet Produce a Source of Relativistic Electrons for the Radiation Belts?. Issue 21 (1st November 2021) - Turner, Drew L.; Cohen, Ian J.; Michael, Adam; Sorathia, Kareem; Merkin, Slava; Mauk, Barry H.; Ukhorskiy, Sasha; Murphy, Kyle R.; Gabrielse, Christine; Boyd, Alexander J.; Fennell, Joseph F.; Blake, J. Bernard; et al.
Abstract: Simultaneous observations from Van Allen Probes in Earth's outer radiation belt (∼4–6 R E ) and Magnetospheric Multiscale (MMS) in the magnetotail plasma sheet at >20 R E geocentric distance are used to compare relative levels of relativistic electron phase space density (PSD) for constant values of the first adiabatic invariant, M. We present new evidence from two events showing: (a) at times, there is sufficient PSD in the central plasma sheet to provide a source of >1 MeV electrons into the outer belt; (b) the most intense levels of relativistic electrons are not accelerated in the solar wind or transported from the inner magnetosphere and thus must be accelerated rapidly (within ∼minutes or less) and efficiently across a broad region of the magnetotail itself; and (c) the highest intensity relativistic electrons observed by MMS were confined within only the central plasma sheet. The answer to the title question here is: yes, it can, however whether Earth's plasma sheet actually does provide a source of several 100s keV to >1 MeV electrons to the outer belt and how often it does so remain important outstanding questions. Plain Language Summary: We used data from NASA's Van Allen Probes and Magnetospheric Multiscale missions to show that the stretched "tail" on the nightside of Earth's magnetosphere can act as a very efficient accelerator of relativistic electrons, moving near the speed of light. With the combination of missions, we show clearly that the acceleration processes in the tail can rival or even surpass the acceleration mechanisms in the outer radiation belt within the inner magnetosphere. This is an important result, since it is current consensus that the radiation belt electrons are accelerated locally, yet these results indicate that the magnetotail has the potential to provide a direct source of relativistic electrons to the outer radiation belt if those electrons are able to be transported inward. Key Points: Earth's magnetotail plasma sheet can provide a source of relativistic (10–100s keV) electrons to the radiation belts Processes internal to Earth's central plasma sheet accelerate relativistic electrons to levels exceeding those in the outer radiation belt The rarity of >∼300 keV injections into the outer radiation belt is not for lack of source in the plasma sheet but for some still unknown reason